Middle Jurassic subduction-related ophiolite fragment in Triassic accretionary complex (Mamu Dağı ophiolite, Northern Turkey). Issue 16 (2nd November 2019) - Çelik, Ömer Faruk; Topuz, Gültekin; Billor, Zeki; Özkan, Mutlu
ABSTRACT: The Mamu Dağı ophiolite, ca. 13 km long and 5 km across (Tokat, Sakarya Zone), consists of peridotites, pyroxenites, gabbros, and basalts, which are crosscut by dolerite dykes. These rocks show variable degrees of serpentinization and alteration. Gabbroic rocks consisting of plagioclase + clinopyroxene ± orthopyroxene ± olivine ± amphibole ± sphene ± opaque minerals have commonly the ophitic and the cumulate textures. Similar mineral paragenesis is observed in the basalts and the dolerites, which are commonly characterized by the sub-ophitic and the microlitic porphyric textures. Primitive mantle-normalized rare earth and trace element diagrams of gabbros and basalts display subduction-related geochemical characteristics such as high Th concentrations, negative Nb, Zr, and Ti anomalies. Some of the gabbros are interpreted to be the cumulate rocks. They have mostly positive europium anomaly (Eu/Eu* 1.77–0.83) and relatively low SiO2 and incompatible element (e.g. Zr, Ti) contents. The initial 87 Sr/ 86 Sr and 143 Nd/ 144 Nd values of gabbro/dolerite and basalt samples vary between 0.7036 and 0.7049, between 0.51259 and 0.51278, respectively. The isotope data and the whole rock geochemistry suggest that the Mamu Dağı ophiolite was derived from a mantle source that was affected by the subduction component rather than MORB or depleted mantle source. Hornblendes from a gabbro sample of the Mamu Dağı ophiolite yielded 40 Ar/ 39 Ar plateau age of 159 ± 1 Ma. This age data is similar to those of many ophiolites located along the İzmir-Ankara-Erzincan suture zone but is different from the ages reported for the Tokat Massif. Graphical abstract: